HOTEL BINTANG EMPAT DI TEPIAN SUNGAI KAPUAS KOTA PONTIANAK - Fitriyah, Fitriyah; Gultom, Bontor Jumaylinda Br; Zain, Zairin (JMARS: Jurnal Mosaik Arsitektur, 2026)
Pontianak City, as the capital of West Kalimantan Province, possesses significant tourism potential, evidenced by a substantial increase in the number of international tourists visiting West Kalimantan. The Pontianak City Government has developed a waterfront area along the Kapuas River to strengthen the city's image and create a new destination; however, it still requires supporting tourism facilities to sustain the productivity of the accommodation service industry. The design methodology was conducted through the collection of both primary and secondary data, which were subsequently analyzed using hotel design theories and neo-vernacular architectural principles. The design results demonstrate that the Four-Star Hotel, designed with seven floors and multiple room types, is capable of providing accommodation, relaxation facilities, recreation, and business meeting spaces that capitalize on the river orientation. The design integrates a Neo-Vernacular approach, combining traditional architectural characteristics with modern technology, including a curved roofline, swimming pool, and landscaped garden positioned near the river as a transitional area toward the waterfront, thus creating an optimal visitor experience along the Kapuas River banks.